(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Among viral diseases, herpes (from the Greek Herpes – fever) occupies one of the leading places. Currently, it is considered the most common human infection. One third of the world’s population is affected by recurrent herpes, and more than half of such patients suffer several attacks of infection per year.